The Tide Was Always High : The Music of Latin America in Los Angeles - Kun, Josh (Book collections on Project MUSE., 2017)
"A collection of essays, interviews, and scholarship exploring the often overlooked history of Latin American musicians and music in the shaping of Los Angeles. Featuring a mix of academics, musicians, and journalists, the book listens to the vibrant Latin American soundtracks of Los Angeles, from Hollywood film sets to recording studios, from vaudeville theaters to Sunset Strip nightclubs, and from Carmen Miranda to Perez Prado and Juan Garcia Esquivel."--Provided by publisher.